(untitled) (The Planet, 2024)
Introduction: Laparoscopic surgery, a groundbreaking minimally invasive technique, has transformed modern surgical practice by enabling procedures with smaller incisions, reduced pain, and quicker recoveries. Initially introduced for diagnostic purposes, it has evolved into a versatile therapeutic approach across various medical specialties. Aim of the study: The aim of the study is to evaluate the advancements and implementation of laparoscopic surgery in a tertiary care hospital of Bangladesh Methods & Materials: This study was conducted at the department of Surgery, Khulna Medical College Hospital, Khulna, Bangladesh, over five years, involving 122 patients who underwent laparoscopic surgery. Adult participants aged 16 and above undergoing general surgical procedures were included, excluding cases with incomplete records or severe comorbidities. Procedures were classified as basic or advanced per SAGES guidelines. Data on demographics, surgical indications, procedure types, and postoperative outcomes were analyzed using SPSS v26. Primary outcomes included the success rate of surgeries, while secondary outcomes focused on postoperative complications and 30-day mortality. Result: The study analyzed 122 participants’ demographics, co-morbidities, surgical histories, indications for laparoscopy, and outcomes. The largest age group was 31-40 years (26.23%), and females predominated (61.48%). Diabetes was the most common co-morbidity (13.93%). Therapeutically, cholelithiasis was the leading indication (34.43%), with laparoscopic cholecystectomy being the most common procedure (33.61%). Appendicitis and laparoscopic appendicectomy followed at 28.69% and 30.33%, respectively. Complications were rare, with superficial infections most frequent. Conservative management (9.02%) was the main intervention, highlighting minimally invasive approaches. Conversion to open surgery occurred infrequently (0.82%). Advanced laparoscopic procedures and associated complications were uncommon. Conclusion: The study underscores the viability of laparoscopic surgery in resource-constrained environments, highlighting its safety, effectiveness, and adaptability. The successful integration of minimally invasive procedures in a tertiary care setting in Bangladesh demonstrates a transformative potential for improving surgical outcomes, emphasizing the importance of adopting advanced techniques in developing healthcare systems.